Geriatric otolaryngology - Sataloff, Robert T.; Johns, Michael M.; Kost, Karen M. (Taylor & Francis, 2015)
A burgeoning elderly population has led to a great increase in the number of geriatric otolaryngology patients, and a comprehensive reference on the specialty will be invaluable in optimizing patient care. Geriatric Otolaryngology, published collaboratively by the American Academy of Otolaryngology-Head and Neck Surgery Foundation (AAO-HNSF) and Thieme, focuses on the unique challenges facing otolaryngologists and primary care physicians in managing ear, nose, and throat disorders in the elderly.It provides readers with the essential information they need to successfully treat this rapidly growing patient population